2016
DOI: 10.1039/c6ra05407b
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metal oxide blended activated coke on flue gas desulphurization

Abstract: The objective of this study was to investigate the possibility of using some natural minerals or industrial waste containing some metal oxides to prepare modified activated coke (M/AC) for flue gas desulphurization. The metal oxides, i.e. Fe 2 O 3 , Co 2 O 3 , CuO and Ni 2 O 3 , were used as additives to prepare M/AC by a blending method. The results show that the M/AC could effectively improve desulphurization performance, and the highest sulphur capacity was obtained at 143 mg g À1 for the Ni/AC sample with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 62 publications
(137 reference statements)
2
28
1
Order By: Relevance
“…In our previous work, copper-modified AC was prepared by a two-step carbonization-activation blending method, in which the carbonization process (600 °C for 1 h) was carried out, and then the carbonized char mixed with metals was activated (950 °C for 1 h). 16 It was found that, compared to the AC, the sulfur capacity of Cu/AC increased by 41.2%. 16 However, for the two-step carbonization-activation blending method, twice heating (carbonization and activation processes) was needed, and a long time was required due to the cooling procedure after carbonization.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our previous work, copper-modified AC was prepared by a two-step carbonization-activation blending method, in which the carbonization process (600 °C for 1 h) was carried out, and then the carbonized char mixed with metals was activated (950 °C for 1 h). 16 It was found that, compared to the AC, the sulfur capacity of Cu/AC increased by 41.2%. 16 However, for the two-step carbonization-activation blending method, twice heating (carbonization and activation processes) was needed, and a long time was required due to the cooling procedure after carbonization.…”
Section: Introductionmentioning
confidence: 96%
“…15 Yang and coworkers found that the introduction of copper species can increase the surface basic sites of Cu/AC, which was favorable for the SO 2 adsorption. 16 Zhao et al reported that the pore width of CuO/AC increased upon CuO addition, which benefited to the adsorption of pollutants from flue gas. 17 Yuan et al pointed out that copper-ore-modified AC facilitated the formation of oxygen-containing functional groups on the ACcopper-ore surface, contributing greatly to the high sulfur capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Among these technologies, surface modication by loading transition metals attracted great attention. 6,16 Natural minerals, rich in transition metals, showed great prospect due to its relatively low cost and the simple preparation procedure when it used as precursor, 17 and the catalytic activity and stability of some kinds of natural minerals for SO 2 and NO removal also have been proved. 18,19 However, it is noteworthy that the formation of metal sulphates during the desulfurization process on the surface of modied AC is unavoidable for almost all the transition metals, and they are difficult to be decomposed under commonly used regeneration temperatures (#500 C).…”
Section: Introductionmentioning
confidence: 99%
“…15,18,19 The transition metals with catalytic activity were typically supported on AC by solution deposition and/or solid blending methods. In recent years, the solid blending method was widely researched, 20 especially low cost natural minerals as catalyst or surface modifier, 21,22 because only soluble metal salts can be used as catalyst. In addition, the preparation of modified AC by the blending method could be completed in one-step carbonization and activation.…”
Section: Introductionmentioning
confidence: 99%